2012
DOI: 10.1007/s10815-012-9758-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-enriched transfer medium improves outcome in patients with multiple embryo transfer failures

Abstract: Purpose To ascertain whether the use of hyaluronanenriched transfer medium (HETM) improves pregnancy and implantation rates among embryo transfer patients with a history of multiple implantation failures. Methods Patients (n0314) under the age of 40 and with a history of multiple unsuccessful embryo transfers were enrolled. There were three groups of patients: those undergoing fresh embryo transfer (fresh ET [n 0111]), those undergoing vitrified-warmed ET in the natural cycle (WET-N [n0101]) and those undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…The ART success rates have been significantly improved over last decades; however, embryo implantation still remains a major limiting factor [1]. It has been considered that composition of an embryo transfer medium is important for interaction between embryo and endometrium at the time of implantation [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ART success rates have been significantly improved over last decades; however, embryo implantation still remains a major limiting factor [1]. It has been considered that composition of an embryo transfer medium is important for interaction between embryo and endometrium at the time of implantation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Both the endometrium of uterine and embryo express receptors for HA. This binding of HA to the embryo might facilitate its attachment to the uterine endometrium until the embryo grows to a hatched blastocyst [1]. Indeed, HA produce a viscous environment that might enhance ET process, while inhibiting the expulsion of embryos from the uterine cavity after ET [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human uterus, peak expression of HAS and CD44 is in the mid-secretory stage (Afify et al 2006). There is a plethora of data suggesting the beneficial roles for HA in human embryo implantation (Urman et al 2008, Hambiliki et al 2010, Nakagawa et al 2012. It is thought that implantation failure could be reduced by providing a 'sticky' matrix for the embryos to attach and for this reason HA (which is also called 'magic glue' (Girish & Kemparaju 2007), or EmbryoGlue (Hazlett et al 2008)) is often used as a supplement in human embryo transfer medium.…”
Section: Embryo Implantation-contrasting Datamentioning
confidence: 99%
“…However, the efficiency and controversy of HA remains inconsistent among different studies. In a few studies, HA was shown to be beneficial for embryo implantation (Svobodová et al 2007;Urman et al 2008;Nakagawa et al 2012). Moreover, in attempts to develop human embryo culture media free from blood-derived additives (particularly albumin) HA was successfully used as a sole macromolecule in human embryo transfer medium, which resulted in high pregnancy and implantation rates (Simon 2003).…”
Section: Gomentioning
confidence: 99%